Perkembangan Bahasa Melalui Metode Bemain Peran Pada Anak Usia 5-6 Tahun Di Taman Kanak-Kanak (TK) Ar-Rahman Samarinda - Heppy Liana; Susanti; Yeni Aslina (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
The objectives of this study are as follows: 1) To determine the language development of children aged 5-6 years at Ar-Rahman Kindergarten (TK) Samarinda. 2) To determine whether role-playing can improve the language development of children aged 5-6 years at Ar-Rahman Kindergarten (TK) Samarinda. This study employed qualitative research methods. Data collection techniques included observation, interviews, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The conclusion of this study is that the language development of children aged 5-6 years at Ar-Rahman Kindergarten (TK) Samarinda is still not optimal in terms of expressive language development. Therefore, stimulation is needed to improve children's language development, namely through role-playing methods. By achieving learning objectives that align with the indicators of expressive language development in children aged 5-6 years, this study has demonstrated that role-playing methods can improve the language development of children aged 5-6 years at Ar-Rahman Kindergarten (TK) Samarinda.